Reimagining crisis teaching through autoethnography: a case of an online Japanese course - Chen, Julian; Sato, Eriko (Taylor & Francis, 2021)
The global pandemic has forced all language teachers, regardless of their affinity to and preparation for online teaching, to convert their face-to-face courses into online versions of crisis teaching. Despite being a crisis, it has also opened opportunities for language educators and researchers to identify innovative ways of evaluating, improving and revamping their current practices. This timely paper reports on emerging issues triggered by emergency remote teaching (ERT), gleaning from the in-depth observations and critical reflections of a Japanese language program coordinator (instructor). Through autoethnography, she provided her first-hand experience and critical reflection on the ERT phenomenon. Qualitative data were gathered from her journal reflections, course evaluations, student assessment outcomes, and communication records documented in Blackboard. The findings pinpoint the following aspects amid ERT: the primacy of tele-/co-presence and the issue of privacy; solutions for online test proctoring and technical malfunction; pedagogically-sound assessment methods in fully online contexts; the balance between asynchronous and synchronous modes and interactions among students. The salient aspects offer best practices that synergize pedagogy and technology for less commonly taught languages delivered in a fully online environment. These valuable lessons learned from ERT can be conducive to future remote teaching in the post-COVID-19 era.